Anthelmintic activity of Ocimum sanctum leaf extract against ovine gastrointestinal nematodes in India. (April 2015) - Kanojiya, Dharmendra; Shanker, Daya; Sudan, Vikrant; Jaiswal, Amit Kumar; Parashar, Rahul
Highlights: In vitro and in vivo efficacy of extracts of Ocimum sanctum on sheep helminthosis. Phytochemical studies to know the active ingredients. Assessment of blood, enzymes and antioxidant parameters for safety trail. Detection of significant anthelmintic efficacy. Abstract: Leaves of Ocimum sanctum have been traditionally used for various ethno-veterinary practices as well as medicinal purpose. In vitro ovicidal and larvicidal potential of crude aqueous and hydro-alcoholic extracts of the bulb of O.   sanctum was investigated. Alkaloids, carbohydrates, steroids and tannins were identified in phytochemical analyses. The various blood parameters coupled marker enzymes and antioxidant status were also evaluated during in vivo trial. Aqueous extract showed better EC50 and EC99 values in comparison with methanolic extract in egg hatch assay and larval development test, respectively. However, in the larval paralysis test, both aqueous and methanolic extracts showed almost similar efficacy. A 77.64% reduction in fecal egg output was observed on day 14. No deleterious ill effect was found in any of the hematological and biochemical parameters suggesting that the plant could be safer for use in sheep.